A NEW PROCEDURE FOR OBTAINING CALCIUM SULPHATE α-HEMIHYDRATE ON THE BASIS OF WASTE PHOSPHOGYPSUM - B. Rajković, M.; V. Tošković, D.; D. Stanojević, D.; Lačnjevac, Č. (Journal of Engineering & Processing Management, 2009)
Investigations, conducted in this study showed that waste phosphogypsum-dihydrate represents a burden which even must not be kept in deposits because of its large quantity in relation to the main product – phosphoric acid, as well as because of great impact of a phosphogypsum deposit on the environment. By the proposed procedure, calcium-sulphate dehydrate is transformed into a far purer α-hemihydrate which, with its physic-chemical characteristics, approaches natural gypsum and contains additional components which enable formation of small-grain phosphogypsum which may be utilised in construction industry. Test installation, given in this study, is highly automated and designed in such way to be operated by only one person. The obtained α-hemihydrate may be utilised for obtaining of gypsum blocks and dry hemihydrate.